Hubungan Frekuensi Konsumsi dan Jenis Junk Food dengan Siklus Menstruasi pada Mahasiswi Fakultas Kedokteran Universitas Mulawarman: Relationship between Frequency of Consumption and Types of Junk Food with Menstrual Cycle in Students of Faculty of Medicine, Mulawarman University - Gresya Elizabet Manurung; Abdillah Iskandar; Alfiani Rachmiputri (Jurnal Sains dan Kesehatan, 2021)
Irregular menstrual cycle is one of the most frequent problems among adolescent girls, such as in medical faculty student of Mulawarman University. This study aimed to determine the association between the frequency of consumption and kinds of junk food with menstrual cycle among female student in medical faculty of Mulawarman University. This was an observational analytic study with cross-sectional design. The subject of this study were 66 female students in medical faculty of Mulawarman University and taken non-randomly using the consecutive sampling method. Food Frequency Questionnaire (FFQ) was used as the instrument to measure the frequency of consumption and kinds of junk food in this study. The result showed that the majority of respondents were 20 years old and getting menarche on 8-14 years old. Most of the respondents have regular menstrual cycle (51,5%), consumed junk food 2-3 days/week (39,4%), and consumed foods made from processed meat or foods that contain high amount of sugar (21,2%). The result of logistic regression test showed that Chi square count less than Chi square table and Sig. more than 0,05. This study concludes that there was no significant correlation between frequency of consumption and kinds of junk food and menstrual cycle. Keywords: frequency of consumption, kinds of junk food, menstrual cycle